The difficulties encountered by first-year English-major students at Academy of Finance when learning the reading skill in the course book Intelligent business (Pre-intermediate) - Lưu, Thị Lan Phương (ĐHNN, 2017)
It is undeniable that out of the four macro English skills, reading is of the most paramount importance to the students at Academy of Finance in general and the students at the Faculty of Foreign Languages in particular. The Intelligent Business series have been used as main textbooks for at FFL and the reading texts in Intelligent Business course book pre-intermediate have exposed some problems to students. Thus, this study is an attempt to discover those difficulties to maximize the students’ interests and success in learning reading. The data obtained from class observation and survey questionnaire for the students at FFL show that the students have problems with their reading texts in course book Intelligent Business in terms of vocabulary, reading skill and background knowledge. Based on the results obtained from data collection instruments, the researcher has come up with some pedagogical implication and suggestions for the students, teachers and the Academy as well. Hopefully, this study will bring about more effective and appropriate solutions to the students at FFL and at the same time, serve as a reference for those who indulge their burning interests in the field of teaching methodology.